The Creeds’ Controversy: The Incarnation and Angels Beliefs According to Nahju al-Balagha - Ali Hussein, Dhoha (Al-Adab Journal, 2019)
Praise be to Allah, the Lord of the Worlds, and prayers and peace be upon the Prophet Mohammed and his household and companions. The doctrine has a central impact on the building of the individual and the community in view of the behavior of the individual and the community. This is the belief: If it is corrupt, it will show the acts of the believers with disadvantages and harms. Hence the need for religious education, and there are various means and ways to pass the doctrine to the minds of its believers. Methods and techniques based on modernity and after following the method of focusing on heritage while preserving the image of the discourse is consistent with contemporary language, and I chose the last type in my research, which relied on the knowledge of the Messenger of Allah whom Allah has given one thousand doors of knowledge. I have focused on Imam Ali’s Nahju al-Balagha as a research sample. Accordingly I divided the research into sections. First: the proper comprehension of the doctrine. Second: the problem of embodiment, and third: the issues of the angels. The paper concluded with a conclusion and a list of sources, and thanks to Allah the god of everything.